Metabolic Alkalosis resulting from a Congenital Duodenal Diaphragm - Annalisa Passariello; Ylenia Maddalena; Monica Malamisura; Silvana Rojo; Nunzia Aragione; Emilia Iaccarino; Giuseppina Franco; Paolo Giliberti (EL-Med-Pub, 2014)
Duodenal diaphragm is an unusual cause of upper intestinal obstruction. We present here a neonate with duodenal diaphragm who presented with features of metabolic alkalosis. Further, an algorithm of management of metabolic alkalosis in a newborn is suggested.